PENTINGNYA MENGHITUNG LABA/RUGI USAHA BAGI UMKM KELURAHAN KRENDANG, KECAMATAN TAMBORA, JAKARTA BARAT - Rina Hartanti; Irma Ade Alisa; Ferinandus Kusuma (ASOSIASI IDEBAHASA KEPRI, 2022)
There are various strategies that need to be carried out so that the pioneered business can develop and be successful, one of which is awareness of the importance of calculating Micro, Small and Medium Enterprises (UMKM) profits/losses. Unfortunately, most Micro, Small and Medium Enterprises (UMKM) only focus on marketing and product development activities. Many Micro, Small and Medium (UMKM) entrepreneurs still think that the calculation of business profit/loss is not too important. Likewise, there are still many Micro, Small and Medium (UMKM) entrepreneurs in Krendang sub-district, Tambora district who do not have the knowledge and skills to calculate business profit/loss. Micro, Small and Medium (UMKM) entrepreneurs in Krendang sub-district, Tambora district really need training that can improve the knowledge and skills of these entrepreneurs in calculating business profit/loss, therefore the Faculty of Economics and Business - Trisakti University in order to help meet the needs of these trainers, cooperate with The Krendang sub-district Apparatus, Tambora District, West Jakarta carries out Community Service (PKM) by providing practical training in calculating business profit and loss, starting from the explanation, understanding and process of calculating Profit/Loss up to the preparation of a business profit/loss report.The results after the PKM implementation were in line with expectations, where participants were very enthusiastic about asking about the calculation of business profit/loss and answering the exercise questions given and answering the questionnaire given, with the assessment getting an average value of 62 to 73 indicating the successful implementation of this PKM training has been in accordance with what is expected. It is expected that compared to the results of the pre-test, it is only around the average value of 46 to 54.